INFORMATION SECURITY: TRADE SECRET MODE REGULATION - Andreevich Baybarin, Andrey; Alekseevich Maximov, Denis; Nikolaevich Dolzhenkov, Valeriy; Sergeevna Artamonova, Yaroslavna; Valeryevich Novikov, Aleksey (Revista Inclusiones, 2020)
This article examines the institution of trade secrets in the legislation of the Russian Federation and its place in the field of information security. Despite a large number of conducted and published studies, a unified approach to the concept of trade secrets has not been developed and the existing legislative definition does not sufficiently express its essence. The purpose of this paper is to reveal the concept of trade secrets through its essential features. The authors investigate the legal framework for regulating the trade secret regime, consider the opinions of scientists about its essence, and compare it with the related concepts of production secret, know-how, and other concepts used by the institute of information security.